Miniaturized broadband high out-of-band rejection bandpass filter based on spoof surface plasmon polaritons with defected ground structure - Yang, Lingling; Liu, Haihong; Cai, Bin; Wu, Ling; Cheng, Yongzhi (Scientific reports, 2024)
In this paper, a novel compact bandpass filter (BPF) with a wide out-of-band rejection is proposed. It can achieve broadband characteristics by combining hollow bowtie-type spoof surface plasmon polaritons (SSPPs) with complementary H-type defected grounded structures (DGSs) through aperture coupling. Compared with the conventional SSPP unit cells, the hollow bowtie-type structure exhibits much better slow-wave characteristics. The introduced slant antenna type port-coupling can produce a very strong high-performance rejection outside the high frequency stopband. Simulation results show that the SSPPs-DGS-based BPF has an excellent band pass characteristics in a broadband range with − 3dB fractional bandwidth of 43.5% at center frequency f 0 of 2.04 GHz. The return loss in the passband is better than − 12 dB. Furthermore, because of the multiple transmission zeros generated in upper-stop-band, the designed BPF has an extremely strong out-of-band rejection of -40dB from 1.5 f 0 to 4 f 0 ( f 0 is the center frequency). The designed SSPPs-DGS-based BPF is fabricated by conventional printed circuit board (PCB) technology with a compact size of only 0.68λ g *0.34λ g (λ g is the wavelength at the center frequency). The measured results have a good agreement with the simulation ones, which verifies the rationality and feasibility of the design. The miniaturized wideband BPF with broad out-of-band rejection may make it has good application prospect in the new generation microwave communication field.